Cu-based alloys as a benchmark for T-PGAA quantitative analysis at spallation neutron sources. Issue 2 (17th December 2019) - Arcidiacono, L.; Martinón-Torres, M.; Senesi, R.; Scherillo, A.; Andreani, C.; Festa, G.
Abstract : In this paper, we present, for the first time, a quantitative analysis carried out using time-resolved prompt gamma activation analysis (T-PGAA), a technique currently under development at the ISIS pulsed Neutron and Muon Source in Oxfordshire. Abstract : In this paper, we present, for the first time, a quantitative analysis carried out using time-resolved prompt gamma activation analysis (T-PGAA), a recent technique currently under development at the ISIS Neutron and Muon Source in Oxfordshire. T-PGAA is a neutron technique based on the radiative capture reaction that allows simultaneous acquisition of the photon energy emitted by the object during irradiation and the time of flight of the neutron that starts the capture reaction. We discuss results from two Cu-based certified standards from MBH Analytical Ltd: a leaded bronze and a brass, in preparation for future applications such as archaeological copper alloys. Results show the validity of the quantitative analysis calculated through a new piece of data analysis software developed in-house for this technique through comparison with the certified values and XRF results.